Filozofia postrzegania. Początki literackie Bolesława Prusa w świetle psychologicznych dociekań Hipolita Taine’a - Jauksz, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article’s aim is to present Bolesław Prus’s [Aleksander Głowacki’s] early literary endavours in the light of the reception of Hippolite Taine’s psychological studies at the turn of the sixties and seventies of the nineteenth century. The Author challenges the common conviction of the fact that Taine’s work has not been a strong point of reference for Prus before 1880 and shows how the strategies of gaining knowledge described by the French philosopher are reflected in the structure and peculiar fragments of Prus’s Warsaw sketches. The syncretism of those literary pieces, that join Prus’s column writing style with journalistic interventionism on the one hand and romantic musings of the literary wanderer, a figure at the core of the stories, on the other allows to show writer’s indecisiveness as a sign of positivistic doubt in approachableness of the nature of reality and of every singular experience.